Huddes Specilla circularia - Vermij, Rienk (Studium, 2018)
This article discusses Hudde’s Specilla circularia, published anonymously and without the name of the publisher in 1656. The only known printed copy was recently acquired by the Royal Library in The Hague. The treatise demonstrates by a mathematical calculation how spherical aberration in lenses can be corrected by means of a diaphragm. Thus, the work offered a theoretical justification for a practice that had already become common by trial and error. The work appears to have been eagerly read and studied by scholars in the second half of the seventeenth century, Spinoza and Leibniz among them, but in the end went into oblivion.